XIX ӘСИР ҚАРАҚАЛПАҚ ӘДЕБИЯТЫНДА ТАРИЙХЫЙ ШЫҒАРМАЛАР - Давлетов, Б. (SCIENCE and SOCIETY, 2017)
The article deals with the study of the process of Karakalpak –Russion relations on the basis of the creation of the classic of the XIX –th century Karakalpak literature Ajiniyaz in tne historical and other materials.